An epidemiological study of cryptosporidiosis at the wildlife/livestock/human interface in Mpumalanga Province, South Africa - Thompson, P.N. (Peter N.) (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.